ANALISIS PENGARUH P-DELTA EFFECT TERHADAP PERBEDAAN KETINGGIAN STRUKTUR GEDUNG TAHAN GEMPA (STUDI KASUS: NON-HIGHRISE BUILDING) - Istiono, Heri; Ramadhan, Azhar Yusuf (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
The need for earthquake resistant buildings in Indonesia is something that needs to be considered. Considering that Indonesia is an earthquake prone area. A building structure must be designed to be able to withstand lateral loads such as earthquakes within the limits set by the code/standards. For conservative reasons analysis of the P-Delta Effect needs to be considered because the building development ratio will always increase every time. according to SNI 1726-2019 the P-Delta effect is only required for the design of tall buildings. In this case, the P-Delta effect will be calculated in the modeling of non-high-rise buildings and get the results that P-Delta Effect increased story forces: moment of the building under 10%.